2019
DOI: 10.1101/793075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strain-Dependent Kinetic Properties of KIF3A and KIF3C Tune the Mechanochemistry of the KIF3AC Heterodimer

Abstract: 250 max) 249 words KIF3AC is a mammalian neuron-specific kinesin-2 implicated in intracellular cargo transport. It is a heterodimer of KIF3A and KIF3C motor polypeptides which have distinct biochemical and motile properties as engineered homodimers. Single-molecule motility assays show that KIF3AC moves processively along microtubules at a rate faster than expected given the motility rates of the KIF3AA and much slower KIF3CC homodimers. To resolve the stepping kinetics of KIF3A and KIF3C motors in homoand het… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…This study has also revealed a profound difference in the behavior of KIF3AC and KIF3AA compared with homodimeric KIF3CC at microtubule intersections. A recent report by Bensel et al (55) provides insight. The authors showed that in the absence of load, KIF3CC homodimers moved much slower than KIF3AA and KIF3AC, and both KIF3CC and KIF3AC backstep as single back steps more frequently than observed for KIF3AA.…”
Section: Navigation Abilities Across All Motors Appear To Be Similarly Influenced By the Structure Of A Microtubule Intersectionmentioning
confidence: 94%
“…This study has also revealed a profound difference in the behavior of KIF3AC and KIF3AA compared with homodimeric KIF3CC at microtubule intersections. A recent report by Bensel et al (55) provides insight. The authors showed that in the absence of load, KIF3CC homodimers moved much slower than KIF3AA and KIF3AC, and both KIF3CC and KIF3AC backstep as single back steps more frequently than observed for KIF3AA.…”
Section: Navigation Abilities Across All Motors Appear To Be Similarly Influenced By the Structure Of A Microtubule Intersectionmentioning
confidence: 94%